A Comparison of the American Model and French (-Inspired) Appellate Model - Blockx, Frederic (2018)
Both the American and the French legal system have a three-tiered structure. However, the respective roles and functions of the courts on each step of the ladder is vastly different in both. Whereas the general system in the U.S. is to have one trial court and two ‘higher’ courts (a court of appeals and a supreme court), the French / European continental system consists of two ‘factual’ courts (the basic level and the court of appeals), and one ‘legal’ (the supreme court) with limited or even inexistent possibilities to look at the facts. The purpose of this thesis is to look at these two models of division of labor between the three tiers through the lens of (i) the procedural leeway each of the courts has and (ii) their focus on fact or law, in function of what questions can be raised in appeal and have to be answered by the courts. We will add Germany to the comparison, as (i) the structure of its court system was inspired by the French, but (ii) has evolved over the years and has been recently (2002) overhauled specifically as to appeals, both to the second level of courts and to the supreme court. We will do so by examining the avenues open for the parties in filing an appeal as well as for the courts in adjudicating those. It will be clear that the distinct philosophies regarding the appellate systems have influence on the entire organization of the different court systems. We conclude that the present-day German system offers the best differentiation of roles between the three tiers while balancing access to the appellate and supreme court level